1998
DOI: 10.1017/s0140525x98001216
|View full text |Cite
|
Sign up to set email alerts
|

A role for ovarian hormones in sexual differentiation of the brain

Abstract: Historically, studies of the role of endogenous hormones in developmental differentiation of the sexes have suggested that mammalian sexual differentiation is mediated primarily by testicular androgens, and that exposure to androgens in early life leads to a male brain as defined by neuroanatomy and behavior. The female brain has been assumed to develop via a hormonal default mechanism, in the absence of androgen or other hormones. Ovarian hormones have significant effects on the development of a sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(74 citation statements)
references
References 264 publications
(315 reference statements)
3
70
0
1
Order By: Relevance
“…These results are consistent with the suggestion that perinatal exposure to estrogens is necessary for femaletypical brains and reproductive behaviors Fitch and Denenberg, 1998;Gerall et al, 1973). It is possible that neonatal ATD altered females' behavior to make them less attractive to males, but similar to Gray and Dewsbury (1973), we did not detect any proceptive behaviors that could have been affected.…”
Section: Defeminization and Feminization Of Prairie Vole Copulatory Bsupporting
confidence: 91%
“…These results are consistent with the suggestion that perinatal exposure to estrogens is necessary for femaletypical brains and reproductive behaviors Fitch and Denenberg, 1998;Gerall et al, 1973). It is possible that neonatal ATD altered females' behavior to make them less attractive to males, but similar to Gray and Dewsbury (1973), we did not detect any proceptive behaviors that could have been affected.…”
Section: Defeminization and Feminization Of Prairie Vole Copulatory Bsupporting
confidence: 91%
“…Estrogen has been shown to be an important modulator of brain development, specifically influencing the plasticity of nociceptive circuits. 97,98 In one study, direct administration of female hormones into the brain induced visceral hypersensitivity in adult female rats. 99 Visceral hyperalgesia can also be induced in male rats by estrogen administration, 100 further demonstrating that estrogen can be a pivotal modulator of visceral pain processing.…”
Section: Sex Linked Differences In Visceral Sensitivitymentioning
confidence: 99%
“…Fetuses of both sexes are exposed to high levels of estrogens from the placenta, perhaps explaining why estrogen does not play a large role in prenatal development. Very little is known about the human behavioral effects of ovarian estrogens during early development (organizational effects) [21] It has been suggested that estrogen's organizational effects occur during early postnatal rather than prenatal development [36,37], but there is no relevant evidence. Progestins from the ovary are thought to have anti-androgenic effects, but there are also reports that they act as androgens [21], and it may be important to consider that effects vary by dose [38].…”
Section: Feminization As An Active or Passive Process?mentioning
confidence: 99%
“…In rodents, these processes are largely dependent on estradiol as it is converted from testosterone in the brain via the action of the aromatase enzyme ('aromatization'). Female rodents are protected from the masculinizing effects of estrogen by a protein which binds circulating estrogen and prevents it from entering the brain [for reviews, see 8,37]. It is unclear whether aromatization is important for human behavior, although the limited evidence suggests that it is not, with masculinization and defeminization resulting directly from the effects of testosterone or other metabolites (see the discussions of Complete Androgen Insensitivity and exposure to diethylstilbestrol, below).…”
Section: Cross-species Comparisonsmentioning
confidence: 99%